Influenza vaccine effectiveness estimates against influenza A(H3N2) and A(H1N1) pdm09 among children during school-based outbreaks in the 2016–2017 season in Beijing, China - Li Zhang; Wim van der Hoek; Thomas Krafft; Eva Pilot; Liselotte van Asten; Ge Lin; Shuangsheng Wu; Wei Duan; Peng Yang; Quanyi Wang (Human Vaccines & Immunotherapeutics, 2020)
Background Since 2007, trivalent inactivated influenza vaccine (TIV) has been provided free-of-charge to primary, middle school and high school students in Beijing. However, there have been few school-based studies on influenza vaccine effectiveness (VE). In this report, we estimated influenza VE against laboratory-confirmed influenza illness among school children in Beijing, China during the 2016–2017 influenza season. Methods The VE of 2016–2017 TIV against laboratory-confirmed influenza virus infection among school-age children was assessed through a case–control design. Conditional logistic regression was conducted on matched case–control sets to estimate VE. The effect of prior vaccination on current VE was also examined. Results All 176 samples tested positive for influenza A virus with the positive rate of 55.5%. The average coverage rate of 2016–2017 TIV among students across the 37 schools was 30.6%. The fully adjusted VE of 2016–2017 TIV against laboratory-confirmed influenza was 69% (95% CI: 51 to 81): 60% (95% CI: −15 to 86) for influenza A(H1N1)pdm09 and 73% (95% CI: 52 to 84) for influenza A(H3N2). The overall VE for receipt of 2015–2016 vaccination only, 2016–2017 vaccination only, and vaccinations in both seasons was 46% (95% CI: −5 to 72), 77% (95% CI: 58 to 87), and 57% (95%CI: 17 to 78), respectively. Conclusions Our study during school outbreaks found that VE of 2016–2017 TIV was moderate against influenza A(H3N2) as well as A(H1N1)pdm09 viruses.